The Urban Conservation Approach of Cittaslow Yalvac - Ozmen, Ayca; Can, Mehmet Cengiz (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2018)
Cittaslow International, which is a network of small cities and towns that embrace the Slow Movement in the field of city management, was founded in 1999 in Italy. As of May 2017, there were 235 Cittaslow cities in 30 countries, and 14 are located in Turkey. The first Turkish Cittaslow community was Seferihisar, which is also the headquarters of the Cittaslow National Network of Turkey. Yalvac, a town and district in the province of Isparta, in the Mediterranean region of Turkey, was accepted as a member of Cittaslow International in 2012. A Project for the protection and development of cultural and environmental values and tourism diversification initiated by the Yalvac municipality; one of the leading heritage non-governmental organizations (NGOs) in Turkey, the Foundation for the Protection and Promotion of the Environment and Cultural Heritage; universities; other NGOs; and the Ministry of Culture and Tourism in the early 2000s, played an important role in obtaining this Cittaslow membership. This study examines the Yalvac case and explores how a historic Turkish town developed an approach to urban conservation years ago, before seeking Cittaslow membership, and how this approach affected its membership in the association and the concept of slowness. It also discusses the interaction between its implementations in the field of urban conservation and its Cittaslow membership in terms of slowness.
Keywords: Cittaslow Movement; Isparta; Slow Movement; tempo giusto; urban conservation; Yalvac; LIFE; Architecture